Ambiental Factors in Parkinson’s Disease Progression: A Systematic Review - Anastasia Bougea; Nikolas Papagiannakis; Athina-Maria Simitsi; Elpida Panagiotounakou; Chrysa Chrysovitsanou; Efthalia Angelopoulou; Christos Koros; Leonidas Stefanis (Medicina, 2023)
Background and Objectives: So far, there is little evidence of the ambient effect on motor and non-motor symptoms of Parkinson’s Disease (PD). This systematic review aimed to determine the association between ambiental factors and the progression of PD. Materials and Methods: A systematic literature search of PubMed, Cochrane, Embase, and Web of Science was conducted up to 21 December 2021 according the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Results: Eight articles were used in the analyses. Long-term exposure to fine particles (particulate matter ≤ 2.5 μm; PM2.5) was positively associated with disease aggravation in two studies. Short-term PM2.5 exposure was positively associated with disease aggravation in three studies. Significant associations were found between PD aggravation and NO2, SO2, CO, nitrate and organic matter (OM) concentrations in two studies. Associations were more pronounced, without reaching statistical significance however, in women, patients over 65 years old and cold temperatures. A 1% increase in temperature was associated with a significant 0.18% increase in Levodopa Equivalent Dose (LED). Ultraviolet light and humidity were not significantly associated with an increase in LED. There was no difference in hallucination severity with changing seasons. There was no evidence for seasonal fluctuation in Unified Parkinson’s Disease Rating Scale (UPDRS) scores. Conclusions: There is a link between air pollutants and temperature for PD progression, but this has yet to be proven. More longitudinal studies are warranted to confirm these findings.